Online accommodation booking habits and attitudes of Serbian travelers - Kalinić, Zoran; Novaković, Miloš (Hotel and Tourism Management, 2019)
The Internet and its services nowadays have significant influence on the organization of our travel arrangements, starting from information gathering to final booking and payment and they are the major distribution channel for travel services and products. The focus of the paper is on digital accommodation platforms, which enable users to search, explore, compare, book and pay online for accommodation all over the world. The study presents habits and attitudes of Serbian consumers to digital travel purchases, particularly accommodation booking. First, the most significant models of online booking systems, such as hotel websites, online tourist agencies and dedicated accommodation booking platforms are presented and compared. The analysis of the habits of Serbian travelers showed that they very often use various websites and online platforms to book their travels, but also that they prefer well-established international platforms, such as Booking.com and Airbnb. They also use online booking more when staying abroad than for domestic stays, and usually book shorter and cheaper travels and stays. As a key advantages of online booking systems, respondents stated wider variety of the offer and time and money savings.